2014
DOI: 10.1002/mc.22205
|View full text |Cite
|
Sign up to set email alerts
|

Akt confers cisplatin chemoresistance in human gynecological carcinoma cells by modulating PPM1D stability

Abstract: Ovarian cancer (OVCA) and cervical cancer (CECA) are lethal gynecological malignancies. Cisplatin (CDDP) and platinum derivatives are first line chemotherapeutics and their resistance impedes successful treatment. Understanding the molecular dysregulation underlying chemoresistance is important in developing rational therapeutic strategies. We have established that Protein Phosphatase Magnesium-dependent 1 D (PPM1D) confers CDDP resistance in gynecological cancer cells by deactivating p53. However, whether CDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
4
24
0
1
Order By: Relevance
“…Akt also inhibits p53 by phosphorylating MDM2 and facilitates its nuclear translocation to promote p53 degradation . We also found that Akt stabilizes the phosphatase PPM1D, which dephosphorylates p53 and Chk1, thereby destabilizing p53 and suppressing its functions …”
Section: Chemoresistance In Gynecologic Cancers and Its Molecular Mecsupporting
confidence: 53%
See 1 more Smart Citation
“…Akt also inhibits p53 by phosphorylating MDM2 and facilitates its nuclear translocation to promote p53 degradation . We also found that Akt stabilizes the phosphatase PPM1D, which dephosphorylates p53 and Chk1, thereby destabilizing p53 and suppressing its functions …”
Section: Chemoresistance In Gynecologic Cancers and Its Molecular Mecsupporting
confidence: 53%
“…Mutation of these two sites significantly inhibited CDDP‐induced apoptosis, suggesting that p53 phosphorylation is needed for p53 function in gynecologic cancer cells. Our work also suggested that chemoresistant gynecologic cancer cells lose their response to CDDP partly due to deactivation of p53 via site‐specific dephosphorylation by protein phosphatase magnesium/manganese‐dependent 1D (PPM1D) …”
Section: Chemoresistance In Gynecologic Cancers and Its Molecular Mecmentioning
confidence: 70%
“…This could be a response of the cell to the stress induced by cisplatin. Furthermore, it was found that PPM1D played an important role in promoting cisplatin resistance, and as a novel downstream target of Akt, PPM1D mediates its action of conferring cisplatin resistance to gynecological cancer cells (41). PPM1D could also be induced by p53 to maintain the homeostasis in cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, cisplatin mediates tumor cell DNA damage and apoptotic function through these signaling pathways, suggesting that Wip1 may be responsible for the cisplatin resistance of ovarian clear cell carcinoma (41). In addition, a recent study demonstrated that Akt confers cisplatin resistance in part through the regulation of PPM1D protein stability, preventing its proteasomal degradation and consequently increasing its half-life (Table I) (42). Accumulating evidence has indicated that Wip1 is directly associated with tumor cell survival and chemoresistance (43).…”
Section: Wip1 In Ovarian Clear Cell Carcinomamentioning
confidence: 99%